(untitled) (Acta Scientiarum. Health Sciences, 2012)
The objective of this research study was to analyze the continuity of activities implemented in a maternity ward in the city of Londrina to improve humanized childbirth assistance. This is an observational study, with a qualitative approach, featuring a study sample of 30 parturient women diagnosed with impending labor, as well as staff, faculty and students, totaling 28 health professionals. The instrument for data collection was based on categories of obstetrical practices of the practical guide for normal delivery assistance from the OMS (1996), which were checked through the observation technique during labor, delivery and postpartum, consisting of variables related to patient obstetric history transcribed from medical records. We observed some positive point; for instance, all women had the company of another person during moments of assistance, privacy in the form of screens and curtains, relaxation techniques, among others. We observed some negative points when the parturient was not given the right to decide on a preferred position for labor, as well as frequent vaginal tests, performed by more than one person. It can be assumed that all implemented measures have discouraged medical-assisted childbirth, and encouraged biomechanical practices and interventions during labor, which are considered more appropriate to the physiology of the procedure.